2017
DOI: 10.1186/s40478-017-0464-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neurologic and cardiac correction by intrathecal gene therapy in Pompe disease

Abstract: Pompe disease is a lysosomal storage disorder caused by acid-α-glucosidase (GAA) deficiency, leading to glycogen storage. The disease manifests as a fatal cardiomyopathy in infantile form. Enzyme replacement therapy (ERT) has recently prolonged the lifespan of these patients, revealing a new natural history. The neurologic phenotype and the persistence of selective muscular weakness in some patients could be attributed to the central nervous system (CNS) storage uncorrected by ERT. GAA-KO 6neo/6neo mice were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 71 publications
2
61
0
Order By: Relevance
“…These results are consistent with those obtained using biochemical glycogen assay performed on AAV9-and AAV10-treated Pompe cardiac muscles. 26 Furthermore, the heterogeneity observed inside the AAV9-treated Pompe mice cluster was in agreement with the variability of the glycogen storage correction previously described in AAV9-treated mice cardiac muscle from GAA and glycogen assay. 26 The results are in accordance with previous studies published by Hordeaux et al 26 that demonstrated a better efficiency of the AAV9 vector for the correction of cardiac muscle in Pompe disease by using conventional approaches as glycogen biochemical assay, GAA enzymatic activity measurements and histological investigations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results are consistent with those obtained using biochemical glycogen assay performed on AAV9-and AAV10-treated Pompe cardiac muscles. 26 Furthermore, the heterogeneity observed inside the AAV9-treated Pompe mice cluster was in agreement with the variability of the glycogen storage correction previously described in AAV9-treated mice cardiac muscle from GAA and glycogen assay. 26 The results are in accordance with previous studies published by Hordeaux et al 26 that demonstrated a better efficiency of the AAV9 vector for the correction of cardiac muscle in Pompe disease by using conventional approaches as glycogen biochemical assay, GAA enzymatic activity measurements and histological investigations.…”
Section: Discussionsupporting
confidence: 87%
“…These biomarkers are routinely analysed by performing biochemical assays and histopathological investigations consisting of glycogen PAS staining and GAA immunohistochemistry on tissue sections. 15,26,[55][56][57] Glycogen PAS staining is based on the principle of periodic acidinduced oxidative cleavage of carbon-to-carbon bounds in 1,2-glycols to form dialdehydes reacting with fuchsinsulphurous acid, which in turn combines with the basic pararosaline, yielding a magenta-like stain. 58 PAS staining could be used to quantify glycogen in tissue sections but the thickness of the sections has to remain constant to ensure the validity of the comparison of glycogen content between sections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 New trials in Pompe disease based on gene therapy are currently ongoing. 12 However, treatment of severe cardiac disease remains quite challenging. [13][14][15] CONCLUSION Typically, patients with infantile-onset Pompe disease and severe hypertrophic cardiomyopathy are not as responsive to enzyme replacement therapy as patients with mild or no hypertrophic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the neuromuscular junction have been linked with glycogen deposits in spinal motor neurons in mice 4 , and infantile-onset patients show secondary symptoms indicative of neural involvement 3,29 . Studies normalizing glycogen levels solely in the brain and CNS in PD mice (using AAV gene therapy) have shown correction of some neuromuscular phenotypes even in the absence of improvement in cardiac or skeletal muscle fibers, demonstrating that a full reversion of clinical phenotypes in PD ERT will require multisystem delivery 30,31 . While we and others have seen a trend or partial reduction in CNS glycogen storage (Supplementary Figure S9) 27 , it remains unknown whether this reduction will be clinically significant in PD patients.…”
Section: Conceptually Any Transmembrane or Cell Surface Protein Thatmentioning
confidence: 99%